Recent Advances in Proteomic Studies of Adipose Tissues and Adipocytes - Eun Young Kim (International Journal of Molecular Sciences, 2015)
Obesity is a chronic disease that is associated with significantly increased levels of risk of a number of metabolic disorders. Despite these enhanced health risks, the worldwide prevalence of obesity has increased dramatically over the past few decades. Obesity is caused by the accumulation of an abnormal amount of body fat in adipose tissue, which is composed mostly of adipocytes. Thus, a deeper understanding of the regulation mechanism of adipose tissue and/or adipocytes can provide a clue for overcoming obesity-related metabolic diseases. In this review, we describe recent advances in the study of adipose tissue and/or adipocytes, focusing on proteomic approaches. In addition, we suggest future research directions for proteomic studies which may lead to novel treatments of obesity and obesity-related diseases.